2020
DOI: 10.1002/jms.4689
|View full text |Cite
|
Sign up to set email alerts
|

Differential proteome analysis of the leaves of lead hyperaccumulator, Rhoeo discolor (L. Her.) Hance

Abstract: The present study investigated Rhoeo discolor (L. Her.) Hance for its ability to accumulate Pb, which is of relevance to phytoremediation applications. Based on this analysis, plants were found to accumulate greater than 10 mg/g (0.1%) of dry weight Pb in the shoots, which classifies the plant a Pb hyperaccumulator. Further, changes in the leaf proteome profiles in response to Pb stress were investigated. Wild-type plants were subjected to a high concentration of Pb(NO 3 ) 2 , and the levels of Pb that accumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 42 publications
(74 reference statements)
0
1
0
Order By: Relevance
“…In a previous study, when the treatment was increased to 1000 μmol·L −1 Pb and Zn for 20 d, the Zn content of the roots of M. cordata exceeded that of Pb [ 21 ], which can be attributed to the serious damage of the roots caused by the high concentration Pb. Pb could easily form Pb-binding compounds with cysteine, non-protein thiols, which caused Pb deposition in vacuoles or cell walls, and decreased the Pb transport in the plants [ 23 ]. It was reported that the levels of cysteine and glutathione were higher in the Pb-accumulating ecotypes of Sedum alfredii than those of the Pb non-accumulating ecotypes [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, when the treatment was increased to 1000 μmol·L −1 Pb and Zn for 20 d, the Zn content of the roots of M. cordata exceeded that of Pb [ 21 ], which can be attributed to the serious damage of the roots caused by the high concentration Pb. Pb could easily form Pb-binding compounds with cysteine, non-protein thiols, which caused Pb deposition in vacuoles or cell walls, and decreased the Pb transport in the plants [ 23 ]. It was reported that the levels of cysteine and glutathione were higher in the Pb-accumulating ecotypes of Sedum alfredii than those of the Pb non-accumulating ecotypes [ 24 ].…”
Section: Discussionmentioning
confidence: 99%